Opportunistic Spectrum Utilization in Vehicular Communication Networks - Cheng, Nan.; Shen, Xuemin (Sherman).; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This brief examines current research on improving Vehicular Networks (VANETs), examining spectrum scarcity due to the dramatic growth of mobile data traffic and the limited bandwidth of dedicated vehicular communication bands and the use of opportunistic spectrum bands to mitigate congestion. It reviews existing literature on the use of opportunistic spectrum bands for VANETs, including licensed and unlicensed spectrum bands and a variety of related technologies, such as cognitive radio, WiFi and device-to-device communications. Focused on analyzing spectrum characteristics, designing efficient spectrum exploitation schemes, and evaluating the date delivery performance when utilizing different opportunistic spectrum bands, the results presented in this brief provide valuable insights on improving the design and deployment of future VANETs.
Introduction -- Opportunistic Communication Spectra Utilization -- Opportunistic Spectrum Access Through Cognitive Radio -- Performance Analysis of WiFi Offloading in Vehicular Environments -- Conclusions and Future Directions.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks